The Relationship Between Abdominal Subcutan Fat Tissue Thickness and HbA1c in Pregnant Women - Aslihan Dilara Demir; Pervin Karli; Durmus Ayan (Medical Network, 2020)
Objective: Obesity is a very common and important health problem and it has become widespread all over the world. Fat tissue is one of the major endocrine organs. Subcutaneous adipose tissue is associated with many diseases such as coronary artery disease, metabolic syndrome, diabetes, impaired lipid profile. Pregnancy is a special condition with metabolic changes involving all systems. We aimed to investigate the relationship and correlation between abdominal fat and HbA1c because of the specific metabolic conditions in pregnancy. Study Design: This is a retrospective study. Ninety-nine (n=99) pregnant women between the ages of 20 and 40 were included in the present study. They have not any other chronic diseases. Ultrasonography was performed between 16.-28. weeks. Abdominal subcutaneous fat tissue was measured during 16-28 weeks of pregnancy. Routine biochemical parameters and HbA1c were evaluated. Results: Subcutaneous fat tissue had a positive correlation with metabolic parameters such as weight and BMI, and a negative correlation with vitamin D level. There is a positive strong correlation with HbA1c level. There was not any correlation between HbA1c and metabolic parameters like triglyceride, LDL, HDL, and cholesterol. Conclusion: There was a strong positive correlation between abdominal subcutaneous fat tissue thickness and HbA1c. However, we didn't find any correlation between infant weight and metabolic parameters.